Fidelity Protocol Development for a Telehealth Type 1 Diabetes Occupation-Based Coaching Intervention. (June 2022) - Shin, Julia; Jewell, Vanessa D.; Abbott, Amy A.; Russell, Marion; Carlson, Kathryn; Gordon, Madison
Background. Preserving fidelity ascertains that the intervention is delivered as intended in occupational therapy (OT) contexts. The process of conceptualizing and developing fidelity standards, however, is seldom documented in the existing literature.Purpose. The purpose of this methodological description paper was to (a) describe the process of generating a comprehensive fidelity plan based on the National Institutes of Health Behavioral Change Consortium's five-domain fidelity framework and (b) evaluate the development process and utility of the end product, the Occupation-Based Coaching (OBC) Fidelity Protocol.Key Issues. There is no known research that documents the process of developing fidelity standards and tools to support the OBC intervention.Implications. The OBC Fidelity Protocol proposes an example of how a comprehensive fidelity plan and tools can be developed from a well-established scientific framework. This can also inform OT practitioners and researchers to deliver OBC sessions with consistency across clients, providers, and interventions/studies.